(untitled) (Web of Teachers: Inderscience Research, 2026)
In the 21st century, the world has become a global, multicultural society, where the borders between countries are no longer physical barriers but rather opportunities for connection. As globalization connects people from various cultural backgrounds more than ever before, the demand for effective foreign language teaching now expands beyond traditional linguistic competence. The concept of intercultural communicative competence (ICC) has emerged as a vital objective in language education. ICC refers to the ability to communicate effectively, appropriately, and respectfully with people from other cultures. The methodology of teaching foreign languages must therefore address both linguistic and intercultural aspects, preparing learners to participate confidently and sensitively in the global community.